2008
DOI: 10.1088/0953-8984/20/38/385212
|View full text |Cite
|
Sign up to set email alerts
|

Testing isotherm models and recovering empirical relationships for adsorption in microporous carbons using virtual carbon models and grand canonical Monte Carlo simulations

Abstract: Using the plausible model of activated carbon proposed by Harris and co-workers and grand canonical Monte Carlo simulations, we study the applicability of standard methods for describing adsorption data on microporous carbons widely used in adsorption science. Two carbon structures are studied, one with a small distribution of micropores in the range up to 1 nm, and the other with micropores covering a wide range of porosity. For both structures, adsorption isotherms of noble gases (from Ne to Xe), carbon tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…The differentiation was performed numerically by the approximation of the data by the empirical function (the results were calculated with the resolution of 0.01 kJ/mol). Finally, the simulated isotherms were fitted by the Dubinin-Astakhov (DA) model, which is one of the most popular equations used in the adsorption area [36,62,63]. The DA adsorption isotherm equation may be written as [46]:…”
Section: Analysing Adsorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation was performed numerically by the approximation of the data by the empirical function (the results were calculated with the resolution of 0.01 kJ/mol). Finally, the simulated isotherms were fitted by the Dubinin-Astakhov (DA) model, which is one of the most popular equations used in the adsorption area [36,62,63]. The DA adsorption isotherm equation may be written as [46]:…”
Section: Analysing Adsorption Isothermsmentioning
confidence: 99%
“…Despite this failure, the utility of Harris et al model is unquestionable. It may be treated as a good model approximation of the microstructure of real activated carbons, as proven, for example, by recovering different experimentally observed empirical correlations [36].…”
Section: Introductionmentioning
confidence: 99%
“…geometric) pore size distribution (PSD) of the VPC models, we applied the method proposed by Bhattacharya and Gubbins [19] and used by us previously (see for example [7][8][9][10][11][12][13][14]). In this method, a uniform grid of points is generated in the simulation box (here 100 Â 100 Â 100) and for each such a point (located in a pore), the largest sphere containing this point (and situated in the pore) is found.…”
Section: Porosity Of Vpcsmentioning
confidence: 99%
“…VPC models are often applied in carbon science and using those models together with molecular simulation techniques it is possible, for example, to analyse the mechanisms of adsorption [2][3][4][5] and immersion [6] and to check the reality of the model of 'hard' carbon proposed by Harris and co-workers [7][8][9][10][11][12][13][14]. Furthermore, the origin of different empirical relationships applied in adsorption science have been studied [9], with the model of Harris et al particularly helpful in understanding the mechanisms of adsorption of different gases (noble gases, benzene, nitrogen, carbon tetrachloride) from gaseous phase [9] as well as the mechanisms of phenol adsorption from aqueous solutions [11]. Since the model presents our conceptualisation of so-called hard activated carbon, in this study, we try to check if similar regularities are observed if one uses the models of 'soft' carbon, obtained using Molecular Dynamics (MD).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the knowledge gained from experiments, simulation methods have been widely developed to model and characterize the nanostructures of carbon [33][34][35][36][37][38][39][40][41]. There are mainly two types of modeling approaches to build structures of nanoporous carbon materials, namely reconstruction methods and mimetic methods.…”
Section: Introductionmentioning
confidence: 99%